Do Flow and Pulsatility Index within the Accepted Ranges Predict Long-Term Outcomes after Coronary Artery Bypass Grafting? - De Leon, Maximiliano; Stanham, Roberto; Soca, Gerardo; Dayan, Victor (The Thoracic and Cardiovascular Surgeon, 2020)
Background Transit-time flow measurement (TTFM) is the gold standard for intraoperative detection of graft failure. Several reports show that TTFM and distal coronary bed quality (DCBQ) may also be useful for midterm detection of graft failure. Nonetheless, there are no data regarding their predictive role on long-term outcomes.Methods Patients with three-vessel disease who underwent isolated coronary artery bypass grafting (CABG) in 2006 and received at least one graft to the left anterior descending artery (LAD) or to the first obtuse marginal (OM1) or posterior descending artery (PDA) were included. Baseline characteristics, mean graft flow, pulsatility index, and subjective impression of DCBQ for each coronary territory were collected. Long-term cardiovascular (CV) and overall survival, operative mortality, and new percutaneous coronary intervention (PCI) were evaluated.Results A total of 177 patients underwent isolated CABG. The OM1 was grafted in 131 patients, the LAD in 169 patients, and the PDA in 100 patients. Neither DQCB nor TTFM were predictors for new PCI. Independent predictors for overall survival were age, previous acute myocardial infarction (AMI), and DQCB of OM1 (odds ratio [OR] = 2.97; 95% confidence interval [CI]: 1.15–7.71). Age, previous AMI, and DCBQ of OM1 (OR = 2.5; 95% CI: 1.39–4.81) were independent predictors for CV survival.Conclusions TTFM on patients with functioning grafts does not predict long-term survival or performance of new PCI. Subjective evaluation of distal coronary bed, especially of the OM1, has a strong impact on long-term outcomes.
Keywords: coronary artery bypass grafts; CABG; coronary artery disease; transit-time flow measurement